The role of financial inclusion and FinTech in addressing climate-related challenges in the industry 4.0: Lessons for sustainable development goals - Mhlanga, David (Frontiers in Climate, 2022)
Individuals and enterprises have an increasing need for financial resources, which has led to the development of numerous financial instruments such as microfinance, insurance, and cash transfers, among other things. The number of development partners advocating for the use of these technologies to address disaster risks and climate change-related concerns is also increasing. With the rise in risk reduction needs and challenges associated with climate change, it's more important than ever to assess the effectiveness of various financial instruments (financial inclusion) in solving climate-related issues. The study used secondary data studied through document analysis to answer the question, "What role does financial technology play in addressing the challenges or hazards associated with climate change in the fourth industrial revolution?" The results indicated that financial inclusion through Fintech could aid in the resilience of households, individuals, and companies in the case of a rapid climate event or the gradual effects of changing rainfall patterns, rising sea levels, or salter water incursion. Insurance, savings, credit, money transfers, and new digital distribution channels can all help victims of climate change and those in charge of dealing with the new environmental realities. As a result, the study advises that financial inclusion through Fintech be promoted as one of the channels that can aid in managing the risks of climate-related concerns and achieving the sustainable development goals through development patterns, governments, and civil society.